1996
DOI: 10.1093/ije/25.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in Coronary Heart Disease and Stroke Mortality among Australian Men, 1979–1993

Abstract: Socioeconomic inequalities in CHD mortality continued to widen during the early 1980s, stabilized thereafter and persisted into the 1990s. Decreases in blood pressure and smoking prevalence contributed most to declines in coronary risk and to socioeconomic differentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
49
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 25 publications
3
49
0
2
Order By: Relevance
“…In Australia, men in manual occupations were 60% more likely to die of stroke than men in professional occupations. 19 A study of elderly women that was conducted in Rotterdam showed that with socioeconomic status (SES) defined according to the occupation of the head of the household, professionals had a significantly lower risk of stroke than manual workers. 20 Adjustment for risk factors had a small effect.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, men in manual occupations were 60% more likely to die of stroke than men in professional occupations. 19 A study of elderly women that was conducted in Rotterdam showed that with socioeconomic status (SES) defined according to the occupation of the head of the household, professionals had a significantly lower risk of stroke than manual workers. 20 Adjustment for risk factors had a small effect.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting poorer dietary profile of those of low socioeconomic position (SEP) may contribute to their higher rates of morbidity and mortality for many health conditions, including type 2 diabetes (4,5) , heart disease (6)(7)(8) , obesity (9)(10)(11) and stroke (6,12) .…”
mentioning
confidence: 99%
“…Recent research suggests that exposure to risk factors operate throughout the life span to influence stroke risk. [5][6][7][8] Of the many explanations for the Stroke Belt examined to date, none provide adequate explanations for geographic differences. 1 Part of the puzzle arises because most studies define Stroke Belt exposure on the basis of state of residence at the time of stroke onset and have not incorporated information on place of residence earlier in life.…”
mentioning
confidence: 99%